The Influence of Depression on the Psychometric Properties of the Maslach Burnout Inventory–Human Services Survey: A Cross-Sectional Study With Nursing Assistants - Trigo, Telma R.; Freitas, Camila C. S. de; Wang, Yuan-Pang; Ribeiro, Floracy G.; de Lucia, Mara Cristina S.; Siqueira, José O.; Iosifescu, Dan V.; Hallak, Jaime Eduardo C.; Fraguas, Renerio (Frontiers in Psychiatry, 2018)
Background: The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) is the most commonly used instrument to assess burnout. Although various factors have been reported to influence its validity, the influence of major depressive episode (MDE) has not been previously considered. We developed this study to investigate the influence of a MDE on the psychometric properties of the MBI-HSS in nursing assistants. Results: From a sample of 521 nursing assistants, we found in those with MDE (n=138, 24.56%) a degree of data misfit into the model, revealed by non-acceptable values for the root mean square error of approximation (RMSEA; 0.073; p=0.004) and for the comparative fit index (CFI; 0.912), while in the non-MDE group these indices were acceptable and good respectively for RMSEA (0.048; p= 0.639) and for CFI (0.951). Also, we found higher coefficients of correlation among MBI-HSS factors and less items loading properly in their respective factors in the MDE subset, when compared to the non-MDE subset. For the total sample, while original 3-factor solution was an acceptable model, the bifactor model fitted data better. Conclusions: MDE may impair the construct validity of MBI-HSS subscales, by increasing measurement error and decreasing model fitness. Therefore, researchers and health professionals should be aware of potential changes in the psychometric properties of the MBI-HSS when applied in subjects with depression.